2007
DOI: 10.1016/j.fertnstert.2006.08.109
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of sexually transmissible pathogens in semen from asymptomatic male infertility patients with and without leukocytospermia

Abstract: Objective-To determine the prevalence of pathogens that cause sexually transmitted infections (STIs) in semen from asymptomatic male infertility patients with and without leukocytospermia (LCS), and associations between STIs, inflammatory markers and other semen variables.Design-Retrospective, controlled study. Results-STI DNA was detected in 45/241 (18.7%) of the samples (CMV 8.7%, HPV 4.5%, HHV-6 3.7%, HSV 3.7%, CT 2.5%, EBV 0.4%, and HBV 0%), with no difference in prevalence between LCS and non-LCS groups. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
167
3
20

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(218 citation statements)
references
References 86 publications
15
167
3
20
Order By: Relevance
“…In the present study, results showed that semen quality declined in male mice infected with PRV, which was similar to the results of previous studies by Kapranos et al (2003) and Bezold et al (2007). The process of spermatogenesis is regulated by a complex interplay of endocrine and paracrine signals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, results showed that semen quality declined in male mice infected with PRV, which was similar to the results of previous studies by Kapranos et al (2003) and Bezold et al (2007). The process of spermatogenesis is regulated by a complex interplay of endocrine and paracrine signals.…”
Section: Discussionsupporting
confidence: 92%
“…The increase of IL-1b expression in the testis during local infection or inflammation is associated with decreased testosterone production and intensity of spermatogenesis (Huleihel and Lunenfeld, 2004), and higher IL-1 concentration have an detrimental effect on sperm motility and fertilization (Anderson and Hill, 1988). Moreover, the sperm count was negatively related to IL-1 level (Bezold et al, 2007), and sperm motility and morphology was negatively related to TNF-a levels (Kocak et al, 2002). In the present research, the concentrations of IL-1b and TNF-a in testis decreased as Thr levels increased.…”
Section: Discussionsupporting
confidence: 50%
“…The passive or active invasion of these bacterial strains induce a generalized or local reaction in the urogenital tract and is often observed as an asymptomatic subclinical inflammation caused by pathogens (50,51).…”
Section: Male Genital Tract Infection and Bacteriospermiamentioning
confidence: 99%
“…In vitro studies have shown significant positive correlations between WBCs in semen and deterioration in total sperm count (50), motility (53,57), morphology (50,57,58) and sperm viability (57).…”
Section: Male Genital Tract Infection and Bacteriospermiamentioning
confidence: 99%
“…In particular, a recent retrospective study explored the prevalence of sexually transmitted infection bacteria in semen samples from asymptomatic male infertile patients with and without leukocytospermia, showing that the DNA of sexually transmitted infection bacteria was detectable in 45/241 (18.7%) of the samples, with no difference in prevalence between the leukocytospermic and non leukocytospermic groups. 5 Bacteriological analyses more frequently reveal different types of microorganisms considered to be the aetiological agents isolated in different biological samples, including urine, expressed prostatic secretions and semen, and on urethral swabs. These germs are Escherichia coli, Klebsiella, Proteus spp., Enterococcus, Staphylococcus spp., Mycobacterium tuberculosis, Neisseria gonorrhea, Chlamydia trachomatis and Ureaplasma urealyticum.…”
Section: Introductionmentioning
confidence: 99%